Analysis of Epstein‐Barr virus and cellular gene expression during the early phases of Epstein‐Barr virus lytic induction. Issue 11 (16th November 2016) - Auburn, Helen; Zuckerman, Mark; Smith, Melvyn
Abstract : N/A: In order to develop novel host/pathogen real‐time PCR assays for routine diagnostic use, early gene expression patterns from both Epstein‐Barr virus (EBV) and Raji cells were examined after inducing the lytic life cycle using 12‐ O ‐tetradecanoyl‐13‐phorbol ester and sodium butyrate. Real‐time PCR identified several highly induced (>90‐fold) EBV lytic genes over a 48 h time course during the lytic induction phase. Latent genes were induced at low levels during this phase. The cellular response to lytic viral replication is poorly understood. Whole human genome microarray analysis identified 113 cellular genes regulated twofold or more by EBV, including 63 upregulated and 46 downregulated genes, over a 24 h time course post‐induction. The most upregulated gene was CHI3L1, a chitinase‐3‐like 1 protein (18.1‐fold; P <0.0084), and the most downregulated gene was TYMS, a thymidylate synthetase (‐7.6‐fold). Gene Ontology enrichment analysis using MetaCore software revealed cell cycle (core), cell cycle (role of anaphase‐promoting complex) in cell cycle regulation) and lymphatic diseases as the most significantly represented biological network processes, canonical pathways and disease biomarkers, respectively. Chemotaxis, DNA damage and inflammation (IL‐4 signalling) together with lymphoproliferative disorders and non‐Hodgkin's lymphoma were significantly represented biological processes and disease biomarkers.